SOME INVESTIGATION ON THE QUALITY OF SMOKED MACKEREL (Rastrelliger sp) USING VARIOUS WOOD WASTE OF LIQUID SMOKE ` - Fronthea Swastawati (JOURNAL OF COASTAL DEVELOPMENT, 2005)
Utilization of liquid smoke as an alternative method of processing fish is becoming more popular nowadays. Mackerel is one of nutritious fish commonly processed as smoked jish. Mackerel fish was dipped into 7,5% salt solutions and 5% liquid smoke of M) sugar-reed waste; (B) teak wood waste; and (C) paddy chajfjbr about I5 minutes, dried in an oven at 50—80°C The average of sensory value of the product was relatively high jar all samples, A= 8.45, B=8. 7I, and C=8.52. Moisture content of the product range 53-58%, protein content 30-32%, fat content 9-I0%,· and ash content x 2%. The highest phenol content was B=6I.46 mg/Kg, while A=43.22 mg/Kg and C=52.30 mg/Kg. The samples A, B, and C all stay in good condition until 3 days of storage in room temperature. Statistical analvsis of proximate data by using SPSS II method resulted p< 0. 05, means that moisture content of A and B was significantly dwerent. Protein content found that A was significantly dyferent compared to B and C Q2 < 0.05). While fat and ash content was not signdicantbv dferent in all samples go > 0.05).